2022
DOI: 10.1155/2022/7570533
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Transcutaneous Electrical Acupoint Stimulation for Postoperative Pain: A Meta-Analysis of Randomized Controlled Trials

Abstract: Objective. This meta-analysis aims to evaluate the effectiveness and safety of transcutaneous electrical acupoint stimulation (TEAS) in treating post-operative pain. Methods. This meta-analysis was registered in PROSPERO (CRD42021286753). We searched PubMed, Embase, and the Cochrane Library for relevant randomized controlled trials (RCTs) about TEAS in treating postoperative pain that were published before November 2021. The primary outcome was visual analogue scale (VAS) within 24 h after surgery. The seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, the analgesic effect of TEAS was also confirmed in this study, as well as the results showed that TEAS significantly reduced VAS scores on the first postoperative day, which was consistent with the findings of a previous meta-analysis on the analgesic effect of TEAS. 31 Considering that unchanged VAS scores were assessed for hip surgery on second postoperative day, we speculate that TEAS could not exhibit a long-term effect of analgesic in such surgery. In addition, we also detected that the intraoperative consumption of propofol and remifentanil was significantly decreased in the TEAS group, 32 which confirmed that TEAS could be an effectively assisted technique for anesthesia.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, the analgesic effect of TEAS was also confirmed in this study, as well as the results showed that TEAS significantly reduced VAS scores on the first postoperative day, which was consistent with the findings of a previous meta-analysis on the analgesic effect of TEAS. 31 Considering that unchanged VAS scores were assessed for hip surgery on second postoperative day, we speculate that TEAS could not exhibit a long-term effect of analgesic in such surgery. In addition, we also detected that the intraoperative consumption of propofol and remifentanil was significantly decreased in the TEAS group, 32 which confirmed that TEAS could be an effectively assisted technique for anesthesia.…”
Section: Discussionmentioning
confidence: 90%
“…Also, it helps restore intestinal peristalsis, eases abdominal pressure, and encourages bowel movements. [34–37]…”
Section: Discussionmentioning
confidence: 99%
“…Also, it helps restore intestinal peristalsis, eases abdominal pressure, and encourages bowel movements. [30][31][32][33] The efficacy of TEAS for postoperative recovery in patient receiving gynecological surgery remains unclear. Some studies have reported significant reductions in postoperative pain, nausea, and vomiting, while others have found no significant differences between TEAS and conventional treatments.…”
Section: Discussionmentioning
confidence: 99%